The Experience of Elderly Hypertension Getting Family Care in Yogyakarta - suratini suratini (International Journal of Health Science and Technology, 2023)
The incidence of hypertension in the elderly which has an impact on increasing morbidity and mortality in hypertension in the elderly. Hypertension is one of the diseases called the silent killer, because hypertension causes various blood vessel complications that can cause coronary heart disease, kidney disease and stroke in the future. The prevalence of hypertension without or with signs of hypertensive heart disease is 33.3%, namely 81 people from 243 elderly people over 50 years. Families have an important role in providing support for the elderly in family care. The purpose of this study was to obtain an overview of the meaning and meaning of hypertensive seniors getting treatment in the family. The number of participants planned for 8 people. The process of retrieving data with in-depth interviews. Analysis of the data used using the steps of Colaizzi. Data analysis in this study with Collaizi technique. The results of the analysis obtained 6 themes, namely the response to hypertension, the cause of increased blood pressure, actions to be taken when hypertension, sources of support for treatment of high blood pressure, views on blood pressure treatment, participants' expectations of high blood pressure and hypertension treatment programs. Suggestions in this research are aimed at families to provide support for daily care in the form of informational support, instrumental, assessment of the elderly so as to be able to make preventive efforts to increase blood pressure.